Interpreting Collocations in the Holy Quran: A Ricoeurian Hermeneutic Study of Five Product Translation Interpretations - Ali Mohammed Saleh Al-Hamzi (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
The Quran is a significant religious text for millions of people worldwide, and its interpretation is of great importance to scholars and researchers in the field of Islamic studies. One area of interest in the Quranic text is the use of collocations, such as "لباس الجوع" (libas aljou), "لباس التقوى" (libas attaqwa), "هن لباس لكم وأنتم لباس لهن" (hunna libas lakum wantum libas lahunna), and "وجعلنا الليل لباسا" (wajalna allayl libasa), which has been the subject of this study. This study aims to explore the interpretation of this collocation in the Quran and compare its translations in various Quranic translations using a Ricoeurian Hermeneutic approach. The analysis is divided into three phases: understanding, explanation, and application, which reveal the cultural influences and underlying meanings behind each translation. By providing a Hermeneutic perspective on collocations in the Quran and presenting a methodology for interpreting sacred texts, this research offers valuable insights for contemporary readers of the Quran and contributes to the field of Islamic studies.